Your Favorite Beverage is an Opportunity to Talk About Chemistry: Didactic Application to the Brazilian High School - Miranda, Mayker; Gonçalves, Gabrielly (Orbital: The Electronic Journal of Chemistry, 2024)
“Let he who has had neither doubts nor difficulties in Chemistry in his school life cast the first pipette.” This science is full of information but it is often limited to formulas, memorization of concepts, experiments in laboratories and activities that only focus on its contents. The world must be seen through the eyes of science which must be used as a tool that helps to explain phenomena of nature so that all knowledge learned in school may be used for benefiting human beings. Therefore, this study aimed at making Chemistry accessible and attractive by using contextualized dialogues about “favorite beverages and their Chemistry”. This study was developed by a High School senior who goes to the Instituto Federal do Triângulo Mineiro - Campus Uberlândia Centro, Uberlândia, Minas Gerais (MG), Brazil. Contextualizing Chemistry was a tool that made teaching easier since students participated and mentioned their favorite beverages, such as soft drinks, coffee, alcoholic drinks and energy drinks. Teachers had the opportunity to teach several chemical concepts, such as methods of separating mixtures, fermentation and molecules, besides chemical structures of sugar, caffeine, ethanol and taurine. Teachers and students also talked about solubility of gas in liquid and dissolution of carbon dioxide in manufacturing of carbonated drinks. This project showed that contextualized Chemistry teaching makes students construct their own learning process.